Os limenites da tolerância religiosa no Brasil do segundo império e a inserção do protestantismo de missão no Recife: (1855-1873). - Santos, Maurício Manoel Amazonas dos (2018)
The present work aims to understand what happened during the Second Empire, when Brazil had an official religion: the Roman Catholic Church. But the arrival of the English and Germans to work in the founding and construction of train lines and their locomotives led to the appearance of temples of worship, where the faithful were to perform services in the mother tongue, but could not catechize Brazilians, not make constructions with appearance of churches, not use bells, cross or candles. They were limited to private worship. Then a serious problem arose: their dead could not be buried in public cemeteries, for these were blessed by the priests and in them only those who had baptistery of the Roman Church could be buried. Here, in the midst of all this, arrived in Brazil, in 1855, the Scot Robert Kalley determined to preach the Gospel to the Brazilians. For this company, it had the help of missionaries from Portugal, but also with important sectors of the Press, Parliament and Freemasonry. What limits and obstacles did Kalley encounter in his mission in Brazil? How did your legal-parliamentary struggle go in facing these limits? What methods did he use to overcome the limits of religious tolerance imposed by the Imperial Constitution and how did he legitimize Protestantism in Brazil? What are the results of your work? These are the main lines of research that guide this work